Formulasi Sediaan Granul Effervescent dari Ekstrak Buah Kurma Ajwa (Phoenix Dactylifera L.) sebagai Sumber Karbohidrat - Liandhajani Liandhajani; Ratih Hardianti (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Ajwa date (Phoenix dactylifera L.) from Medina, Saudi Arabia, contains a high carbohydrate content. Dates are commonly recognized to be available in two forms: dried fruit that may be consumed directly and concentrated date juice. Concentrated date juice usually gives an unpleasant taste when consumed and requires a large container for storage. This study aims to formulate the effervescent granules using two combinations of acids, namely citric acid and malic acid as a source of acid and sodium bicarbonate as a source of base. The research process was began with macerating dates with 96% ethanol solvent and making a dry extract. Furthermore, effervescent granule preparations were made in three formulations with the ratio of sodium bicarbonate and acid (citric acid : malic acid) as follows: formulation I = 2.5: (2:1), formulation II = 3: (2:1), formulation III = 3.5: (2:1). The results showed that, each 5g serving size contained 84.41 g of carbohydrate in the form of effervescent granules. In formula I, the test results obtained were pH 4.82, water content 4.14%, flow speed 11.58 g/second, angle of repose 25.36o, and dispersion time 28.91 seconds. Then, in formula II, the test resultedin pH 5.27, water content 3.80%, flow speed 12.39 g/second, angle of repose 26.69o and dispersion time 26.19 seconds. Moreover, the test findings for formula III, were pH 5.76, water content 3.86%, flow speed 11.83 g/second, angle of repose 26.63o and dispersion time 29.55 seconds. The differences between acid and base concentration ratio in the three formulas above affect the physical properties of effervescent granule preparations, with formula II producing the best carbonation of the three.